Prototyping of a CO detection system in subway parking garages using arduino nano - Rodriguez, Richard (2024)
The present work focuses on detecting carbon monoxide in underground parking lots using a robot controlled by Arduino Nano. Equipped with specific sensors, an LCD screen, and a rechargeable lithium battery, the robot performs initial inspections, with damped servomotors for efficient mobility. Obstacle detection is carried out using an ultrasonic device, and the data is recorded in real-time on the EMQX server. To reduce mortality rates and protect operators from exposure to toxic gases, this project accurately measures environmental parameters, highlighting the importance of servomotors in vehicle movement.